"Unicorn horn" drugs in the medical and pharmaceutical culture of Europe - mateusz dąsal; Aleksander Smakosz; Wiktoria Kurzyna; Michał Rudko (Polish Pharmaceutical Society, 2021)
In modern pharmaceutical science, raw materials of animal origin are a rarity. However in the 19th century horns, tusks, skeletons or various secretions of animals were widely used in medicine by physicians and pharmacists. One of them was the supposed "unicorn horn," shortly called alicorn. From the perspective of an Evidence-Based-Medicine, finding such as an alicorn in old pharmacopoeias and dispensatories is rather surprising. Nevertheless, for a long time unicorns were considered to be real. A big part in spreading this belief was the Bible, which formerly even scientists had to recognise as an indisputable source of knowledge. Recipes for medication containing alicorn can be found in the Pharmacopoeia Cracoviensis (Kraków Pharmacopoeia) by Jan Woyna from 1683. The alicorn was believed to have alexipharmic, perspiration-promoting, antipyretic, aphrodisiacal, antiulcer, antiepileptic, heart-strengthening and cephalic (counteracting mental disorders) properties. The extraordinary medical properties of the alicorn, especially the ability to detect poisons, have affected its price, to the point that at the peak of its fame it reached prices equivalent of a few villages or a manor. The ability to detect poisons was quite useful for kings and other people in power, who were often targets of poisoners. Obtaining an alicorn on a royal court was prestigious and fashionable. The name of the "unicorn horn" was given to twenty different raw materials, usually of animal origin, classified into two groups by apothecaries - the real alicorn (unicornum verum) and its equivalents (unicornum falsum). Among those twenty raw materials, a narwhal tusk (unicornu marinum), a fossilized mammoth tusk (unicornu fossile) or a rhino horn (rhinocerotis cornus) were found. What is crucial, the rhino horn is still employed in Traditional Chinese Medicine in the treatment of severe cases of COVID-19. In pharmaceutical practise the alicorn was mostly used in the pharmaceutical preparations such as powders, potions, electuaries and morsels. The existence of the mythical horn and its medical properties was finally disclaimed in the 19th century. The aim of this paper is summarising the natural history of cornu unicorni, especially in European medicine and analysing the alicorn-based formulae,